PENENTUAN PENYEBARAN DAN PERHITUNGAN SUMBERDAYA RESERVOAR COALBED METHANE PADA FORMASI MUARA ENIM, BLOK Y, CEKUNGAN SUMATERA SELATAN DENGAN PENDEKATAN MODEL 3-D GEOSELULLER - , DWI KURNIAWAN SAID; , Dr. Ir. Jarot Setyowiyoto, M.Sc., dan Dr. Arifudin Idrus, S.T., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Y block is a coalbed methane (CBM) exploration block. This block was overlapped by conventional oil development block. In order to obtain a wellrounded perspective of the block-coalbed methane reservoir, the necessity of data integration between the CBM exploration wells and conventional oil wells is a must. However, such integration is not often going smoothly. The differences of data quality and resolution which resulted from different measurements become a great barrier. In addition, data measurements information are also frequently encountered in different scales so various reservoir modeling approach was needed to complete a puzzle of its CBM reservoir conditions. One of the approach is a 3-D geocelullar model. 3-D geocelullar model is a new approach in a coalbed methane research. This approach is intended to generate a threedimensional modeling of a reservoir close to the real models. The advantage of using this approach is its application in a limited data condition, because of the basis-approach is in the form of geostatistical method.Therefore, reservoir models obtained will not be in speculative nature but rather interpolative. In addition, by the process of generating reservoir model, it also enables to used to calculate the total resources of reservoir. The objective of applying the approach in this research is to analyze the distribution and resources calculation of coalbed methane reservoir in Muara Enim Formation, Y Block, South Sumatera Basin. The results of coalbed methane reservoir analysis distribution shows the distribution of coalbed methane reservoir is developed in North East-South West orientation of continuous-delta plain environment with maximum thickness (35-55 ft) encountered in the slope areas. While, the resources calculation exhibits the total resources of coalbed methane in this block reaches 2.1 TCF.